La figure du dictateur dénoncée : art et politique dans les années 1970 à la Dominique (Petites Antilles) - Marvin Fabien (Études Caribéennes)
This article examines, through a historical and aesthetic approach, the relationship between art and politics in the 1970’s in the island of Dominica. During this period, the Caribbean islands were in search of identity. The relationship that these islands had with their colonizers appeared to be in a phase of transformation which led little by little, for some islands, towards local governance and a total autonomy.The Prime Minister of Dominica in 1974, Patrick John, seemed to reincarnate the power of the colonizer. However, in Dominica, the black people’s awareness of their social and political situation, influenced by the advent of black identity movements, such as the ‘Black Power Movement’ in the United States and the Rastafari movement in Jamaica, initiated in many individual's contempt for the abuse of power. In this context, artists of this period such as Alwin Bully, playwright, Christian George and Kelo Royer, visual artists and activists of the Rastafari movement, were able, by their creations, to influence and criticize the political powers of their time. Patrick John later suffered the fall of his government and imprisonment probably because of his draconian laws and his attempted overthrow of government after his defeat.